Financing corporate tax cuts with shareholder taxes - Alexis Anagnostopoulos; Orhan Erem Atesagaoglu; Eva Cárceles-Poveda (Quantitative Economics, 2022)
We study the aggregate and distributional consequences of replacing corporate profit taxes with shareholder taxes, namely taxes on dividends and capital gains, in a setting with incomplete markets and heterogeneity at both the household and the firm level. The reform yields distributional gains with a large majority of households benefiting. Moreover, if dividend and capital gains are taxed at the same rate, the reform is also efficiency-enhancing and the implied optimal corporate income tax rate is zero. In contrast, an asymmetric tax treatment of dividend and capital gains induces a trade-off between efficiency and distributional concerns that is optimally resolved at a positive optimal corporate tax rate, implying double taxation.
Keywords: E6; 330; double taxation; heterogeneity; misallocation; Optimal corporate taxes